x^2+y^2-2x+2y=23 in the form of (x-a)^2+(y-b)^2=c
Dealing with the equation of a circle!!!
Did anybody actually answer this for you? First, rewrite as (x^2 - 2x) +(y^2 + 2y) = 23 To complete the square we need a constant term in each of the sets of parentheses that is equal to one half of the linear term, squared. In both cases this is the number 1 So you then have (x^2 - 2x +1) + (y^2 +2y +1) = 25 (addint 2 to each side. Both the terms in parentheses are now perfect squares, so your are left with (x - 1)^2 + (y + 1)^2 = 25 This is the equation of a circle of radius 5, with center at (1,-1). Graph it and see!